P24 Regional experience of indications for switching patients to raltegravir and maraviroc and success after regimen change. (23rd May 2012) - Clarke, E; Bhardwaj, A; Sundaram, S; Rowen, D; Foley, E; Samraj, S
Abstract : Background: In small centres there is wide variation in the accessibility of raltegravir (RAL) and maraviroc (MVC) as they are not on the formulary of several trusts. Individual PCT funding is sought on a named patient basis, a time consuming process leading to potential delays in treatment. Objectives: To identify common clinical indications for treatment change to RAL or MVC. To formulate prescribing criteria on the basis of these in order to seek approval from the District Prescribing Committee and streamline treatment provision. Methods: Retrospective case note review of patients started on RAL or MVC attending six HIV clinics within a regional network between 2008 and 2010 and collection of data on reasons for treatment change. Results: 40 patients were reviewed, 37 of whom started RAL and 3 MVC. Multiple factors contributed to therapy change. 22 patients (55%) had resistance to other antiretrovirals or treatment failure and 20 (50%) had significant side effects or intolerance to other drug classes. Other factors included cardiovascular risk (20%), co-infections (18%) and co-morbidities (18%). 14 patients were reviewed for immunological response following treatment. Two were excluded (one unrelated death). Of the remaining 13 patients, 46% had a suppressed viral load prior to starting RAL, and 92% were suppressed after 12 months of treatment. Conclusions: This study demonstrates that identifying common indications for switching to RAL and MVC within a regional network supported the process of formulating criteria to prescribe these newer drugs. This unified approach within the region led to improved and timely access to these drugs thereby improving outcomes for patients at small centres. The agreed prescribing criteria were in instances where combination therapy was not possible due to intolerability, side effects, allergies, resistance, drug interactions, co-morbidities, or HIV-2 (for RAL).